Stumped by Headlines: Investigating a Functional Knowledge Deficit - Ungar, Sheldon (Canadian Journal of Higher Education, 2002)
Competing claims about the level of ignorance, or knowledge, among the current Nexus generation are addressed. The core of the paper is a theoretical analysis of ignorance in the knowledge society. Specifically, the knowledge-ignorance paradox suggests that the intense specialization demanded by a knowledge economy militates against a broader information society and gives rise to "reading reluctance." To provide evidence for this analysis, the results of a small-scale study testing the idea of a "functional knowledge deficit" are presented. Students were asked to identify metaphorical terms that are commonly used without definition in newspaper captions. The results revealed that students could only identify about 30% of these common expressions, and that they did not do better with terms derived from computers or the popular culture. Significant differences were also found between male and female responses. Both the implications of the findings and further avenues of research are discussed.